Acetylcysteine in random skin flap in rats - Abla,Luiz Eduardo Felipe (2005)
PURPOSE: Analyze the ability of Acetylcysteine to reduce distal necrosis in a random skin flap, in the rat. METHODS: The present study utilized 28 adult male Wistar-EPM rats distributed, at random, in two groups of 14 animals. Control group rats (CG) received distilled water and Acetylcysteine group animals (NACG) received NAC (300 mg/kg) by oral infusion, 15 minutes before flap elevation. On the seventh postoperative day, percentage of distal necrosis was determined and skin samples collected in order to allow determination of MDA levels. RESULTS: The mean necrotic area in CG group (control) was 66 % and in NACG group (Acetylcysteine) 52 %, a statistically significant difference according to the Mann-Whitney test (U calc = 25; U crit = 45). MDA levels were lower in the CG flap skin samples than in the NACG samples (U calc = 24; U crit = 45), the oposite being true in the normal skin samples (U calc = 10; U crit = 45). CONCLUSION: Acetylcysteine was effective, according to the model used, reducing the percentage of distal necrosis in NACG rats.